An Aristotelian Rhetorical Analysis Of Joe Biden’s Inaugural Speech - Khelaifa, Aissa; Mhamdi, Nadhir (University of Ammar Theledji -Laghouat, 2022)
This research endeavors to shed light on the rhetorical and persuasive techniques used by the current American President Joe Biden in his inaugural speech which marks the beginning of a new term in office. Joe Biden stands as his previous political leaders who passed from this mission and had better understanding of the effective political speech, in this frame, Biden’s persuasive strategies are mainly based on the Aristotle Rhetoric Appeals which have been explored in this work that he used to persuade the American audience. The goal of this study is to reveal the role that Rhetoric Persuasive technique played in Biden’s inaugural speech. In order to achieve this aim, the entire speech is analyzed from the perspective of CDA and the typical modes and the strategies associated with the Aristotle Rhetoric Theory. The Aristotelian Rhetorical Analysis shows that Biden used the three Aristotelian Modes: Ethos, Pathos and Logos. Pathos is the most mode used over Ethos and Logos. Besides that, Biden managed to use other Rhetoric tools like Speech Acts, Deictic, Metaphor and Repetition as persuasive strategies to make his speech mostly effective